Scientific Writing Training for IAIN Ambon Students - Aria Bayu Setiaji; Enggal Mursalin (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Abstract. This community service activity (PkM) specifically aims to, 1) provide understanding to students about tips and tricks for writing scientific papers, 2) improve students' skills in writing scientific papers, and (3) improve the quality of student scientific papers. The training participants were 30 IAIN Ambon students consisting of students from the Faculty of Tarbiyah and Teacher Training (FITK) and the Faculty of Sharia and Islamic Economics (FSEI). The materials presented during the training included 1) Basic Concepts of Writing Scientific Writing, 2) Anatomy of Scientific Writing, 3) Use of Language in Scientific Writing, and 4) Tips and Tricks to Overcome Plagiarism. The methods used during the training were lectures, demonstrations, interactive discussions and coaching clinics. The results of this PkM activity are, 1) students gain basic knowledge about the preparation of scientific works such as articles, proposals and theses, 2) students are able to compose scientific papers in accordance with systematics and writing criteria, and 3) students are able to write scientific papers that quality.Keywords: systematics of scientific writing, paraphrasing, plagiarism, language formulation